KESADARAN HUKUM MASYARAKAT DALAM JUAL BELI TANAH DENGAN AKTA PPAT DI KECAMATAN TINANGGEA KABUPATEN KONAWE SELATAN SULAWESI TENGGARA - Rifan Agrisal Ruslan; Umar Ma’ruf (Jurnal Akta, 2017)
The purpose of writing in this study is the first, to know and analyze factors Some people in Tinanggea Sub-District South Konawe Regency of Southeast Sulawesi that has not yet had legal awareness in the act of buying and selling land ownership in the presence of PPAT. Second, To know and Analyze Efforts - Local Government efforts in awakening the community in District Tinanggea South Konawe Southeast Sulawesi against the sale and purchase of land ownership in the presence of PPAT. Third To know to be done in order to Maasyarakat in Tinanggea Sub-District of Konawe Selatan Regency in Sulawesi Teggara performs the sale and purchase of land ownership in the presence of PPAT.The approach method used in this research is empirical juridical. Juridically, this research is based on the rule of law of Basic Agrarian Law and Government Regulation Number 37 Year 1998 juncto Government Regulation Number 24 Year 2016. Empirically, this study aims to know about the rules related to the transfer of land rights with the fact that occurred that deviate from the rules that prevail in the District Tinanggea South Konawe Southeast Sulawesi. Specification of Research that is the object of research is the plot of land is the transfer of Rights to Land with the act of buying and selling of land ownership in the presence of PPAT conducted. Sources and Techniques Data collection is primary data obtained from interviews conducted by 30 respondents and secondary data obtained from the opinions of scholars and literature review. Then Theory in use is Position Theory, Authority Theory and Theory of Legal Certainty.From the results of research can be concluded that the legal consciousness of the people of Tinanggea Sub-District of South Konawe Regency of Southeast Sulawesi is related to the transfer of land rights due to the sale and purchase of land ownership in the presence of the First PPAT: Caused by lack of PPAT and PPATS in the community, which is set by the competent authorities, Caused by a very high kinship and Due to a very low legal community awareness. The second is the government's efforts in the form of socialization held by the local revenue agency related Value Object Tax (NJOP), Tinanggea sub-district office along with jejerannya Kelurahan and village appealed and made a place for reporting / consultation related to the transfer of rights of Sale and Purchase of Land, Cooperation undertaken by Tinanggea Subdistrict Sub-District and Village that make the Letter of Statement of Physical Land Mastery (SPPFT) that the letter is known by Kecamatan Kelurahan and Desa. The third is: The ideal concept of the author's research is the legal counseling to the public to grow knowledge to the public about the importance of legal awareness of the act of buying and selling land ownership in the presence of PPAT, Socialization of the sale and purchase of land ownership in the presence of PPAT. As a form of government service to the public in awakening the rights and obligations of the people in the eyes of the law and Data Collection and the making of Land Book is aimed to record and provide a legal protection for the community so that no land grab or land disputes.Keywords: Legal Awareness, Sale and Purchase, Tinanggea Sub-district.